Investigation of HMX‐Based Nanocomposites. Issue 2 (30th October 2014) - Patel, Rajen B.; Stepanov, Victor; Swaszek, Sean; Surapaneni, Ashok; Qiu, Hongwei
Abstract Advanced munition systems require explosives which are more insensitive, powerful, and reactive. For this reason, nano‐crystalline explosives present an attractive alternative to conventional energetics. In this study, formulations consisting of 95 % octahydro‐1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetrazocine (HMX) and 5 % polyvinyl alcohol (PVOH) were prepared with mean crystal sizes ranging from 300 nm to 2 μm. The process to create these materials used a combination of mechanical particle size reduction and spray drying, which has the advantages of direct control of crystal size and morphology as well as the elimination of ripening of crystals (which occurs during slurry coating of nanomaterials). The basic physical characteristics of these formulations were determined using a variety of techniques, including scanning electron microscopy and X‐ray diffraction. Compressive stress‐strain tests on pressed pellets revealed that the mechanical properties of the compositions improved with decreasing crystal size, consistent with Hall‐Petch mechanics. The 300 nm HMX/PVOH composition demonstrated a 99 % and 129 % greater strength and stiffness, respectively, than the composition with 2 μm HMX. The formulations were subjected to the Small Scale Gap Test, revealing a significant reduction in shock sensitivity with decreasing crystal size. The formulation containing 300 nm HMX registered a shock initiation pressure 1.6 GPa above that of the formulation with 2 μm HMX, a 44 % improvement in sensitivity. These results serve to highlight the relevance of structure‐property relationships in explosive compositions, and particularly elucidate the substantial benefits of reducing the high explosive crystal size to nano‐scale dimensions.